Morphology and Facade Study of Umah Pitu Ruang (Case Study: Umah Edet Reje Baluntara in Toweren Village, Aceh Tengah) - Zulfikri Zulfikri; Muhammad Heru Arie Edytia; Elysa Wulandari; Pratitou Arafat; Farisa Sabila (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2023)
Aceh Tengah is home to various tribes, notably the Gayo tribe, known for their unique houses and philosophies with rich historical significance. One such house, Umah Edet Reje Baluntara in the Toweren Uken village, has stood for over a century, bearing historical traces, particularly in its changing morphology over time. This research uses a qualitative descriptive method that consists of two stages, namely collecting secondary data from various online literacies to become the initial basis for describing Umah Edet Reje Baluntara and collecting primary data as field data which is carried out directly at the location of Umah Edet Reje Baluntara by interviewing trusted sources. and observe the object. This data was processed to reconstruct Umah Edet Reje Baluntara by digitizing it using SketchUp Pro 2022 software. Reconstruction via software found several changes in materials and space. These changes are caused by natural factors, family, and time that has passed for a long time. Since this house was built in 1860, the changes in shape that have occurred are in the serule roof elements which have changed to tin roofs, the natural stone ompak foundation has changed to cast concrete, the Titi construction has been lost, elements of the stairs and stair doors are also missing, space the kitchen at the back has been dismantled, the pepir ornaments have been damaged, and many of the lisplang ornaments have been broken.